Media Pembelajaran Interaktif Berbasis ICT Dalam Pendidikan Agama Islam - arin, arin arin (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2018)
The purpose of this research is to produce valid and effective ICT-based PAI learning media. This research was conducted using research and development design from Borg and Gall, and used an ICT-based analytical technique approach. Based on the results of assessment needs, the study of theory and the results of research that a learning strategy applied by the teacher will depend on the approach used; whereas how to implement the strategy can be determined by various learning methods. In an effort to carry out the learning method the teacher can determine the technique that he considers relevant to the method, and the use of the technique, each teacher has a strategy that may differ between teachers and each other. Keywords: PAI Learning Media, interactive, ICT